Completeness and Accuracy of Immunization Status and Smoking Habits Associated with the Incidence of Acute Respiratory Infections in Toddlers in the Kaliasin Health Center Working Area - Rohman Daka; Nurul Aryastuti; Dina Dwi Nuryani; Wayan Aryawati (Postgraduate, University of Mataram, 2023)
ARI is the leading cause of infectious disease morbidity and mortality in the world. Nearly four million people die from ARI every year. According to WHO in 2016, the morbidity and mortality rate of ARI is quite high, especially in toddlers. ARI is the number one cause of infant mortality in Indonesia. South Lampung Regency ranks first in the number of ARI cases in children under five every year. The purpose of this study was to determine the factors associated with the incidence of ARI in toddlers. This study is a quantitative study with Cross Sectional design with a population of 2,578 toddlers and a sample of 126 toddlers. The sampling technique used was purposive sampling using univariate and bivariate analysis tests using Chi Square. Toddlers who experience ARI 39.7%, toddlers who have complete immunization status 62.7%, toddlers who have completeness and accuracy of immunization status 27.0% and who have smoking habits 57.9%. There is a relationship between completeness of immunization (p-value = 0.000) with OR 4.450 (CI 2.057-9.624), completeness and accuracy of immunization (p-value = 0.000) with OR 5.553 (CI 1.976-15.607) and smoking habits (p-value = 0.000) with OR 9.419 (CI 3.747-23.677) with the incidence of ARI in toddlers. It is expected that health workers can increase promotive and preventive efforts to the community in the form of counseling or socialization to provide knowledge related to ARI disease